Transformational leadership and patient safety in hospital nursing practice: A scoping review - Adil Setia Gulo; Yakobus Siswadi; Ni Gusti Ayu Eka (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Patient safety is a key component of healthcare quality and remains a global priority. Nurses play a central role in maintaining patient safety, and leadership is recognized as an important organizational factor influencing safety outcomes. Transformational leadership has been widely applied in nursing; however, evidence linking it directly to patient safety outcomes remains fragmented. Purpose: To map and synthesize evidence on the role of transformational leadership in influencing patient safety outcomes in hospital nursing practice. Method: This scoping review followed the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines. Literature searches were conducted in PubMed, MEDLINE with Full Text (EBSCO), and ScienceDirect for studies published between 2020 and 2025. The PCC framework was used as the basis for formulating the research questions and selecting articles. Studies examining transformational leadership and patient safety outcomes among hospital nurses were included. Data were extracted and analyzed using narrative thematic synthesis. Results: Four studies met the inclusion criteria. Four main themes were identified: transformational leadership as a foundation for patient safety culture, indirect influence through psychosocial and work environment factors, impact on nurses’ safety practices and reporting behaviors, and contextual and organizational influences. All studies reported positive associations between transformational leadership and patient safety outcomes. Conclusion: Transformational leadership supports patient safety by promoting a positive safety culture, improving safety practices, and enhancing workforce well-being. Further longitudinal and intervention studies are needed to strengthen causal evidence and guide leadership development.